The Role of Internal Auditor of Government Companies: Perceptions of the Auditee - Fuada, Nurul (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
This study aims to determine the auditee's perception of the role of internal auditors in one of the government companies, namely PT. PLN (Persero) Sulselrabar Main Unit. The research data was obtained from a questionnaire (primary) on employees (as auditees) which were distributed to 30 respondents. There are three variable dimensions used, namely the role of internal auditors as supervisors, consultants, and catalysts. Based on the research results it is known that the role of internal auditors as supervisors has an average value (mean) ranging from 2.87 to 3.37, while for the role of internal auditors as consultants has an average value ranging from 3.00 to 3.40, and for the role of internal auditors as a catalyst has an average value ranging from 2.90 to 3.27. So it can be concluded that the auditee's perception indicates that the role of the internal auditor at PT. PLN (Persero) Main Unit for Sulselrabar Region has been quite effective in its implementation. This can be seen from all of these variables the respondent (auditee) gives a positive perception of the role of the internal auditor